The Effect of Bacteria on Seed Germination in Sorghum and Rape Under Cadmium and Petroleum Conditions - Shuang, Shao; Zhenfang, Gui; Xiaolei, Guo (International Journal of Biotechnology for Wellness Industries, 2016)
A large amount of oil hydrocarbons and heavy metals have been discharged into the environment and caused soil polluted. Petroleum and cadmium in soil accumulated in crops and lead to threaten human healthy through the food chain. In this experiment, seeds of sorghum and rape were germinated in deferent concentrations of petroleum and cadmium, and the effect of Peptococcus activus sp. SH3-3-9 on the germination was studied. The results showed that petroleum and cadmium inhibited seeds germination, and the effects were stronger as their concentrations increased. Peptococcus activus sp.SH3-3-9 had the role of enhancing seed germination, which indicates it has high potential in plant-microbial remediation of petroleum and cadmium in soil.